2015
DOI: 10.1002/art.39107
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Gut Microbiota and the Metabolite‐Sensing Receptor GPR43 in a Murine Model of Gout

Abstract: Objective Host–microbial interactions are central in health and disease. Monosodium urate monohydrate (MSU) crystals cause gout by activating the NLRP3 inflammasome, leading to interleukin‐1β (IL‐1β) production and neutrophil recruitment. This study was undertaken to investigate the relevance of gut microbiota, acetate, and the metabolite‐sensing receptor GPR43 in regulating inflammation in a murine model of gout. Methods Gout was induced by the injection of MSU crystals into the knee joints of mice. Macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
181
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(206 citation statements)
references
References 45 publications
8
181
0
3
Order By: Relevance
“…C4 inhibits ROS production in neutrophils stimulated with N-formylmethionyl-leucylphenylalanine via cAMP, and a PTX-sensitive release of G protein G bg complex. Conversely, C2 increases ROS production in a PTX-insensitive manner (Vinolo et al, 2009), and macrophages lacking FFA2 do not produce ROS in a model of gouty arthritis (Vieira et al, 2015). This may reflect opposing signaling via FFA2 and Ga q/11 and FFA3 and Ga i/o .…”
Section: Physiologic Roles Of Ffa2/ffa3mentioning
confidence: 99%
“…C4 inhibits ROS production in neutrophils stimulated with N-formylmethionyl-leucylphenylalanine via cAMP, and a PTX-sensitive release of G protein G bg complex. Conversely, C2 increases ROS production in a PTX-insensitive manner (Vinolo et al, 2009), and macrophages lacking FFA2 do not produce ROS in a model of gouty arthritis (Vieira et al, 2015). This may reflect opposing signaling via FFA2 and Ga q/11 and FFA3 and Ga i/o .…”
Section: Physiologic Roles Of Ffa2/ffa3mentioning
confidence: 99%
“…Once again, the effects of raising the mice GF were reversed by exogenous administration of SCFAs. 278 Finally, GF mice have also been used to link the gut microbiota to the function of FFA2 in adipose tissue, where in one study FFA2 −/− mice were found to be obese compared to wild-type mice when raised under conventional conditions but were not different from wild type when raised GF. 263 A number of studies have also assessed the function of FFA3 using similar approaches.…”
Section: Ffa2 Ffa3 and The Gut Microbiotamentioning
confidence: 99%
“…Monosodium urate monohydrate crystals cause gout by activating the NLRP3 inflammasome, which leads to IL-1β production and neutrophil recruitment. In germ-free mice, the production of shortchain fatty acids that are necessary for adequate inflammasome assembly and IL-1β production is decreased 85 . This effect depends on the metabolite-sensing receptor free fatty acid receptor 2 (also known as G-protein coupled receptor 43) 85 .…”
Section: Evidence From Animal Studiesmentioning
confidence: 99%
“…In germ-free mice, the production of shortchain fatty acids that are necessary for adequate inflammasome assembly and IL-1β production is decreased 85 . This effect depends on the metabolite-sensing receptor free fatty acid receptor 2 (also known as G-protein coupled receptor 43) 85 . Overall, observations in some experimental models of arthritis show that microbial triggers by commensal bacteria are required to promote disease in genetically predisposed animals.…”
Section: Evidence From Animal Studiesmentioning
confidence: 99%